ТHE ROLE OF GENETIC TESTING FOR OPTIMAL ANTIPLATELET THERAPY SELECTION IN THE TREATMENT OF CORONARY ARTERY DISEASE PATIENTS - S. T. Matskeplishvili; Y. E. Arutyunova (Кардиоваскулярная терапия и профилактика, 2014)
The studies of coronary heart disease as a cause of reduced life quality and disability in population led to improved methods of diagnosis and treatment of this disease. To date, accumulated large evidence base supports the use of DAT (dual antiplatelet therapy) in patients with coronary artery disease after PCI. According to the same data some patients still develop severe complications, i. e. stent thrombosis. In this regard, recent years there is increasing importance of the genetic testing for selection of the optimal antiplatelet therapy in patients with coronary artery disease.